Comprehensive Survey of PCV2 and PCV3 in Domestic Pigs and Wild Boars Across Portugal: Prevalence, Geographical Distribution and Genetic Diversity - Bernardo Almeida; Margarida D. Duarte; Ana Duarte; Teresa Fagulha; Fernanda Ramos; Tiago Luís; Inês Caetano; Sílvia C. Barros; Fábio Abade dos Santos; Ana Margarida Henriques (Pathogens)
Porcine circoviruses are significant pathogens that affect swine populations worldwide, with implications for animal health and productivity. While PCV2 is well-documented, particularly due to widespread vaccination programs, PCV3 is less understood, and its epidemiological impact is still under investigation. This study screened for PCV2 and PCV3 in pigs and wild boars across Portugal to assess their prevalence. Also, nucleotide sequence determination was performed to evaluate the genetic diversity of these viruses. Stool samples from 160 pigs belonging to different groups (quarantine, nursery, fattening and adult pigs), as well as organ samples from 120 hunted wild boars, were analyzed. Samples were collected from twelve of the eighteen mainland Portuguese districts with positive cases being detected in nine of them. Pigs had a lower prevalence of PCV2 (1.9%) than PCV3 (11.2%), but the opposite was true in wild boars (76.7% for PCV2 and 55.0% for PCV3). The lower PCV2 prevalence in pigs can be attributed to the PCV2 vaccination program implemented. Additionally, these viruses were significantly more prevalent in wild boars (90.8% were infected with at least one of the viruses) than in domestic pigs (only 12.5%). This significant difference highlights the impact of the controlled environment in pig farms on disease prevention in contrast to the higher exposure risks faced by wild boars in their natural habitat. Compared to a previous study from 2023, we observed a slight decrease in the percentage of positive cases for both PCV2 and PCV3. Phylogenetic analysis of sequences obtained by Sanger sequencing allowed us to conclude that the samples from domestic pigs belong to the PCV2a and PCV3c clades, in contrast to the PCV2-positive cases detected in domestic pigs in 2023 that were classified in the PCV2d genotype. Conversely, samples from wild boars belong to the PCV2d and PCV3a clades. These results reveal genotype differences between wild and domestic pigs and shifts from 2023 to 2024. Our findings provide some information about the circulation of these viruses and emphasize the importance of vaccination and continued monitoring for a deeper understanding of their epidemiology to mitigate potential risks to swine health and production.